2023
DOI: 10.3390/ijms242216295
|View full text |Cite
|
Sign up to set email alerts
|

The Unknown Role of Periostin in Psoriatic Epidermal Hyperplasia

Milena Wojciechowska,
Kinga Ścibior,
Monika Betyna-Białek
et al.

Abstract: Psoriasis is an inflammatory skin disease that affects 1–2% of the general population. The pathomechanism is based on type 1 immunological reactions. Hyperplasia of the epidermis in psoriasis is a result of disrupted epidermal architecture due to increased synthesis and expression of extracellular matrix proteins. In our study, we analyzed the involvement of periostin (POSTN) in the pathogenesis of psoriasis, as one of the extracellular matrix proteins belonging to the fasciclin family. The study group consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
3
0
0
Order By: Relevance
“…The latter finding is in agreement with previous results where only mild deposition of POSTN in the same dermal locations was reported in normal skin 44 . However, in two recent studies, POSTN was also found in the epidermis of PS patients, while the overall expression in relation to normal skin was reduced 45 or not evaluated 46 . Similarly to our findings, Wojciechowska et al.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The latter finding is in agreement with previous results where only mild deposition of POSTN in the same dermal locations was reported in normal skin 44 . However, in two recent studies, POSTN was also found in the epidermis of PS patients, while the overall expression in relation to normal skin was reduced 45 or not evaluated 46 . Similarly to our findings, Wojciechowska et al.…”
Section: Discussionsupporting
confidence: 94%
“…44 However, in two recent studies, POSTN was also found in the epidermis of PS patients, while the overall expression in relation to normal skin was reduced 45 or not evaluated. 46 Similarly to our findings, Wojciechowska et al did not detect POSTN in the skin of a portion (34%) of the patients. 46 Due to these discrepancies, the role of POSTN in PS needs more attention as well as the herein reported differences with AD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation